Repeated Bout Rate Enhancement Is Elicited by Various Forms of Finger Tapping - Emanuelsen, Anders; Voigt, Michael; Madeleine, Pascal; Kjær, Pia; Dam, Sebastian; Koefoed, Nikolaj; Hansen, Ernst A. (Frontiers in Neuroscience, 2018)
Voluntary rhythmic movement, such as for example locomotion and other cyclic tasks, are fundamental during everyday life. Patients with impaired neural or motor function often take part in rehabilitation programs, which include rhythmic movements. Therefore it is imperative to have the best possible understanding of control and behavior of human voluntary rhythmic movements. A behavioural phenomenon termed repeated bout rate enhancement has been established as an increase of the freely chosen index finger tapping frequency during the second of two consecutive tapping bouts. The present study investigated whether the phenomenon would be elicited when the first bout consisted of imposed passive finger tapping or air tapping. These two forms of tapping were applied since they can be performed without descending drive (passive tapping) and without afferent feedback related to impact (air tapping) - as compared to tapping on a surface. Healthy individuals (n=33) performed 3-min tapping bouts separated by 10 min rest. Surface electromyographic, kinetic and kinematic data were recorded. Supportive experiments were made to measure e.g. the cortical sensory evoked potential response during the three different forms of tapping. Results showed that tapping frequencies in the second of two consecutive bouts increased by 12.9%±14.8% (p<0.001), 9.9%±6.0% (p=0.001), and 16.8%±13.6% (p=0.005) when the first bout had consisted of tapping, passive tapping, and air tapping, respectively. Rate enhancement occurred without increase in muscle activation. Besides, the rate enhancements occurred despite that tapping, as compared with passive tapping and air tapping, resulted in different cortical sensory evoked potential responses. Based on the present findings it can be suggested that sensory feedback in an initial bout increases the excitability of the spinal central pattern generators involved in finger tapping. This can eventually explain the phenomenon of repeated bout rate enhancement seen after a consecutive bout of finger tapping.